Perovskite Solar Cells: Record Open‐Circuit Voltage Wide‐Bandgap Perovskite Solar Cells Utilizing 2D/3D Perovskite Heterostructure (Adv. Energy Mater. 21/2019). Issue 21 (4th June 2019) - Gharibzadeh, Saba; Abdollahi Nejand, Bahram; Jakoby, Marius; Abzieher, Tobias; Hauschild, Dirk; Moghadamzadeh, Somayeh; Schwenzer, Jonas A.; Brenner, Philipp; Schmager, Raphael; Haghighirad, Amir Abbas; Weinhardt, Lothar; Lemmer, Uli; et al.
Abstract : In article number1803699, Ulrich W. Paetzold and co‐workers develop a novel 2D Ruddlesden–Popper perovskite interlayer by solution processing n‐butylammonium bromide on wide‐bandgap double‐cation perovskite absorber layers (EG ≈ 1.72 eV). The devices with this 2D/3D heterostructure induce a high open‐circuit voltage of up to 1.31 V, which leads to very high stable power output efficiencies of up to 19.4% for wide bandgap perovskite solar cells.